2015
DOI: 10.1371/journal.pone.0115513
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Colonisation Sequence Are Key Parameters Driving Cooperation and Competition between Pseudomonas aeruginosa Cystic Fibrosis Strains and Oral Commensal Streptococci

Abstract: Cystic fibrosis (CF) patient airways harbour diverse microbial consortia that, in addition to the recognized principal pathogen Pseudomonas aeruginosa, include other bacteria commonly regarded as commensals. The latter include the oral (viridans) streptococci, which recent evidence indicates play an active role during infection of this environmentally diverse niche. As the interactions between inhabitants of the CF airway can potentially alter disease progression, it is important to identify key cooperators/co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 37 publications
3
65
0
1
Order By: Relevance
“…Several bacterial species detected in the CF respiratory microbiome here were also considered as the most frequent oral commensal bacteria such as Streptococcus , Prevotella , Porphyromonas , Rothia , Tannerella , Fusobacterium ,… This result confirmed the close relation between respiratory and buccal microbiotas due to microaspirations of salivary and potentially explained by the neutral dispersion model recently proposed [3739]. In addition regarding the co-presence of Pseudomonas and oral commensal bacteria, there is recent evidences showing that the oral commensal streptococci could modulate the growth of Pseudomonas in CF disease condition [40]. …”
Section: Discussionsupporting
confidence: 77%
“…Several bacterial species detected in the CF respiratory microbiome here were also considered as the most frequent oral commensal bacteria such as Streptococcus , Prevotella , Porphyromonas , Rothia , Tannerella , Fusobacterium ,… This result confirmed the close relation between respiratory and buccal microbiotas due to microaspirations of salivary and potentially explained by the neutral dispersion model recently proposed [3739]. In addition regarding the co-presence of Pseudomonas and oral commensal bacteria, there is recent evidences showing that the oral commensal streptococci could modulate the growth of Pseudomonas in CF disease condition [40]. …”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, colonization sequence is also important for the ability of oral commensal streptococci to inhibit P. aeruginosa. S. gordonii and S. sanguinis inhibit the P. aeruginosa Liverpool epidemic strain in an H 2 O 2 -dependent manner when these streptococci are inoculated as the primary colonizer in the presence of CO 2 (Whiley et al, 2015), which is consistent with our previous and current studies that demonstrate H 2 O 2 -producing streptococci inhibit a chronic and acute isolate of P. aeruginosa in the presence of nitrite when oral commensal streptococci are the primary colonizers (Scoffield & Wu, 2015). Overall, more studies are required to strengthen our understanding of how H 2 O 2 -producing commensal streptococci and nitrite can negatively impact P. aeruginosa virulence.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed examination of the interaction between DWW2 and 3a in a hypercapnic environment (10% CO 2 ) demonstrated increased virulence factor (pyocyanin) expression by the pseudomonad when in co-culture as seen previously with an LES and AGS partnership and between wound strain PAO1 and streptococci from the oropharynx [27,28,29]. The results from this study also demonstrated that the increase in pyocyanin was not due to increased expression throughout the biofilm but to the development of discrete pigmented areas within the biofilm that were dominated by the high pyocyanin expressing, non-mucoid phenotype together with higher numbers of the streptococcus which in turn was associated with an increased conversion of strain DWW2 from mucoid to non-mucoid.…”
Section: Discussionmentioning
confidence: 83%